A critical review of the arguments against the use of rubrics - Panadero, Ernesto; Jonsson, Anders (Educational research review, 2020)
Rubrics are widely used in classrooms at all educational levels across the globe, for both summative and formative purposes. Although the empirical support for the benefits of using rubrics has been steadily growing, so have the criticisms. The aim of this review is to explore the concerns and limitations of using rubrics as proposed by the critics, as well as the empirical evidence for their claims. Criticisms are then contrasted with findings from studies reporting empirical evidence in the opposite direction (i.e. supporting the use of rubrics). A total of 27 publications were identified, and 93 excerpts were extracted, after a detailed content analysis. The criticisms were organized around six broad themes. One of the main findings is that the empirical evidence behind criticisms is, with only a few exceptions, neither direct nor strong. On the contrary, several critics refer to anecdotal evidence and/or personal experiences, which have limited value as scientific evidence. Another finding is that a number of critics make claims about rubrics with a narrow conceptualization of rubrics in mind. One prevalent assumption is that rubrics are only used for high stakes testing and/or other summative assessment situations. Based on these findings, we advocate a more pragmatic approach to rubrics, where potential limitations of rubrics are investigated empirically and decisions are based on scientific data. •Rubrics are popular assessment tools that have received considerable criticism.•Our aim was to explore the focus and empirical evidence behind this criticism.•27 publications were identified, 93 excerpts were extracted and organized into six themes.•Only a few studies provided empirical support for their claims.•Rubrics seem to have more benefits than drawbacks, especially when used formatively.